Continuous Delivery and DevOps – A Quickstart Guide : Start your journey to successful adoption of CD and DevOps, 3rd Edition /: Start your journey to successful adoption of CD and DevOps, 3rd Edition. (2018) - Swartout, Paul
No abstract available